The spectrum of in vitro maturation in clinical practice: the current insight - Ahmad, Mohd Faizal; Elias, Marjanu Hikmah; Mat Jin, Norazilah; Abu, Muhammad Azrai; Syafruddin, Saiful Effendi; Zainuddin, Ani Amelia; Suzuki, Nao; Abdul Karim, Abdul Kadir (Frontiers in Endocrinology, 2023)
In-vitro oocyte maturation (IVM) has been used worldwide. Despite long-term implementation, the uptake of this procedure to complement current in-vitro fertilization (IVF) remain low. The main reason is likely due to the non-synchronization of protocol and definition criteria leading to difficulty in collective proper outcome data worldwide, thus, lack of understanding of the exact IVM procedure. The review aims to consolidate the current clinical practice of IVM by dissecting relevant publications to be tailored for a current spectrum of clinical practice. Nevertheless, the background theories of oocyte maturation were also explored to provide a comprehensive understanding of the basis of IVM theories. Additional discussion of other potential uses of IVM in the future, such as in ovarian tissue cryopreservation known as OTO-IVM for fertility preservation and among Diminished Ovarian Reserved (DOR) women, was also explored. Otherwise, future collaboration among all IVM centers is paramount for better collection of clinical data to provide valid recommendations for IVM in clinical practice, especially in molecular integrity and possible DNA alteration if present for IVM offspring outcome safety purposes.